CSIG-09. ATRX DEFICIENCY IN GLIOMA IMPACTS TRANSCRIPTIONAL PROFILES AND THE IMMUNE MICROENVIRONMENT IN VIVO. (9th November 2020) - Irvin, David; Roberts, Hannah; Sharin, Vladislav; Farooqi, Ahsan; Dharmaiah, Sharvari; Alvarez, Christian; Huse, Jason
Abstract: Current treatment for diffuse astrocytoma fails to address its underlying molecular mechanisms leading to inevitable disease progression and eventual patient death. Genomic studies have implicated ATRX alterations as critical to low grade glioma biology. Our lab has previously shown in vitro that ATRX influences glioma motility, cellular differentiation state, and epigenetic programming, however, the influence of ATRX alterations in vivo remains unclear. Here, we leveraged an RCAS/tva mouse tumor model to probe the role of ATRX deficiency in glioma. Atrx deficient murine tumors exhibited lower histopathological grade and were associated with longer survival than Atrx-intact counterparts, and syngeneic allografts of cell lines derived from primary tumors mirrored the differential degrees of aggressiveness seen in primary tumors. Tumor-derived Atrx-deficient cell lines showed increased susceptibility to G-quadruplex stabilizing compounds, pointing to increased replication stress and recapitulating a key phenotype of ATRX-mutant gliomas in humans. Transcriptional profiling revealed enrichments in MYC target genes, E2F targets as well as G2/M checkpoint pathways in Atrx-intact tumors and cells, and enrichment in RAS signaling in Atrx-deficient tumors and cells. Finally, Atrx deficient murine gliomas displayed increased levels of NK cells, a phenotype recapitulated in ATRX-mutant human gliomas, and primary Atrx-deficient glioma lines exhibited increased levels of NK cell-attracting cytokines. These latter findings suggest that ATRX deficiency could influence interactions between glioma cells and their immune microenvironment by way of phenotypically relevant molecular mechanisms.